A companion to the American West - Deverell, William, 1962- (Blackwell companions to American history., 2004)
A rigorous introduction to the history of the American West. Over 20 essays by expert scholars synthesize the best work in the field. Each essay covers a subtopic of American Western history, its major concerns and its major works to provide an overview of themes and historiography.